2023
DOI: 10.1158/1541-7786.c.6545012.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Data from TSC2 Interacts with HDLBP/Vigilin and Regulates Stress Granule Formation

Abstract: <div>Abstract<p>Tuberous sclerosis complex (TSC) is caused by mutations of either the <i>TSC1</i> or <i>TSC2</i> tumor suppressor gene. TSC causes tumors of the brain, heart, kidney, skin and lymphangioleiomyomatosis (LAM). Here we report that the TSC2 protein physically binds to high-density lipoprotein binding protein (HDLBP), also called vigilin, a core stress granule (SG) protein, and that TSC2 localizes to SGs. SGs contain mRNAs and translation initiation complexes, and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Likewise, the S. cerevisiae RPTOR orthologue KOG1 and TOR1 localize to SGs (Takahara and Maeda, 2012). Also the TSC subunit TSC2 (Kosmas et al, 2021) and the mTORC1 substrates S6K1 and 2 (Sfakianos et al, 2018) have been recently reported at SGs (Figure 2), which might impinge on mTORC1 activity as well. It will be interesting to delineate the coordination of the recruitment and disassembly of the TSC and mTORC1 complexes and their substrates at SGs.…”
Section: Sgs Inhibit Mtorc1mentioning
confidence: 88%
See 1 more Smart Citation
“…Likewise, the S. cerevisiae RPTOR orthologue KOG1 and TOR1 localize to SGs (Takahara and Maeda, 2012). Also the TSC subunit TSC2 (Kosmas et al, 2021) and the mTORC1 substrates S6K1 and 2 (Sfakianos et al, 2018) have been recently reported at SGs (Figure 2), which might impinge on mTORC1 activity as well. It will be interesting to delineate the coordination of the recruitment and disassembly of the TSC and mTORC1 complexes and their substrates at SGs.…”
Section: Sgs Inhibit Mtorc1mentioning
confidence: 88%
“…In contrast, mTORC1 inhibition has been shown by several studies to reduce SG formation upon heat shock, arsenite, and the proteasome inhibitor Bortezomib (Fournier et al, 2013;Mazan-Mamczarz et al, 2015;Sfakianos et al, 2018;Heberle et al, 2019). Conversely, TSC2 deficiency, known to hyperactivate mTORC1, increases the number of SGs formed upon arsenite or heat stress (Kosmas et al, 2021). As discussed above, mTORC1 activity under stress is enhancedat least in partby PI3Ks and MAPK14 (Heberle et al, 2019).…”
Section: Control Of Sg Formation By Mtorc1mentioning
confidence: 98%